NOTE ON THE PRAWN FISHERY IN THE GULF OF KUTCH DURING 1962-63 - Deshmukh, V M (Indian Journal of Fisheries, 2011)
The monsoon fishery of August-September in the creeks, and the winterfishery of October-November in the gulf form the two main prawn-fishing seasonsin the Gulf of Kutch. The monsoon fishery is supported by Metapenaeus kutchensis,while the winter fishery, by M. kutchensis, M. hrevicornis and Penaeusindicus. The pattern of distribution of these species indicates that there is a higherabundfuice of M. kutchensis in the Inner gulf and P. indicus and M. brevkornisin the outer gulf.The average growth rate of juveniles of M. kutchensis is found to be 6.7mm per month. Sex-ratio distribution shows preponderance of females in thecatches. The fluctuation in the landings of the monsoon months shows correlationwith the salinity of the creek; relatively better landings occur coinciding with thelowering of salinity.